CLINICAL AND LABORATORY CHARACTERISTICS OF RENAL PATHOLOGY OF PREGNANCY IN THE FIRST TRIMESTER - Berdiyarova Shokhida Shukurullayevna; Murtazaeva Nasiba Komilzhonovna (TADQIQOTLAR.UZ, 2024)
The significant spread of kidney diseases, their medico-social significance and the disabling nature of the pathology determine the special relevance of the problem of early diagnosis and prevention of diseases of the urinary system in pregnant women. The effect of urinary tract diseases on the course of childbirth, pregnancy and the postpartum period, as well as on the condition of the fetus and newborn, has been studied by many researchers [1, 2, 3]. The issues of etiology and pathogenesis of urinary tract infection during pregnancy are widely covered in the literature. Most authors note the leading role of bacteria in the occurrence of the disease, both during pregnancy and outside it, especially representatives of the Enterobacteriaceae family [6, 7].